Analisis Kontribusi Badan Usaha Milik Desa (BUMDES) terhadap Pendapatan Asli Desa (PAD) Desa Kesiman Kertalangu - Yakub Ndara Kambu; A. A. Sagung Mirah Indukirana; I Wayan Sedia (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The problem in this research is that the contribution of Village-Owned Enterprises (BUMDES) in improving the economic life of the people of Kaluku Village, North Luwu Regency has not been felt evenly by the community. This research aims to determine the contribution of Village-Owned Enterprises (Bumdes) of Kaluku Village in improving the economic life of the community and an overview of Islamic Economics on the contribution of Village-Owned Enterprises (Bumdes) of Kaluku Village in improving the economic life of the community. The research method used is a qualitative method. The data sources used are primary data obtained through interviews and secondary data obtained through important documentation of the Village-Owned Enterprises (Bumdes) of Kaluku Village, North Luwu Regency. Data were processed and analyzed using qualitative descriptive methods. The results of this research show that (1) The contribution of Village-Owned Enterprises (BUMDES) in Kaluku Village, North Luwu Regency in improving economic life, among others, through providing loan funds, providing seminars, training and consultation in managing businesses (2) Islamic Economics Review of The contribution of Village-Owned Enterprises (BUMDES) is in accordance with the principles of Islamic economics because it is mutually helpful so it is recommended in Islam but in the implementation of BUMDES it is contrary to Islamic economics because it uses an interest system so it is prohibited in Islam. The implication of this research is that by referring to the research results, the Bumdes in Kaluku Village should be managed optimally so that the benefits can be felt evenly by the community.